2021
DOI: 10.3389/fnagi.2021.746982
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-Scanner Variability of Automated Brain Volumetry on Three Magnetic Resonance Imaging Systems in Alzheimer’s Disease and Controls

Abstract: Magnetic Resonance Imaging (MRI) has become part of the clinical routine for diagnosing neurodegenerative disorders. Since acquisitions are performed at multiple centers using multiple imaging systems, detailed analysis of brain volumetry differences between MRI systems and scan-rescan acquisitions can provide valuable information to correct for different MRI scanner effects in multi-center longitudinal studies. To this end, five healthy controls and five patients belonging to various stages of the AD continuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
1
13
1
1
Order By: Relevance
“…The scan-rescan variability observed in our study, both within and across scanners, compares well with those previously reported for volumes ( Wittens et al, 2021 ; De Guio et al, 2016 ; Jovicich et al, 2009 ; Kruggel et al, 2010 ; Yang et al, 2016 ; Fujita et al, 2019 ; Vavasour et al, 2019 ; Deprez et al, 2018 ), cortical thickness ( Fujita et al, 2019 ; Kecskemeti et al, 2021 ; Mcguire et al, 2017 ) and diffusion metrics ( Acheson et al, 2017 ; Grech‐Sollars et al, 2015 ; Kamagata et al, 2015 ; Liu et al, 2014 ; Palacios et al, 2017 ; Prohl et al, 2019 ; Shahim et al, 2017 ; Veenith et al, 2013 ; Zhou et al, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…The scan-rescan variability observed in our study, both within and across scanners, compares well with those previously reported for volumes ( Wittens et al, 2021 ; De Guio et al, 2016 ; Jovicich et al, 2009 ; Kruggel et al, 2010 ; Yang et al, 2016 ; Fujita et al, 2019 ; Vavasour et al, 2019 ; Deprez et al, 2018 ), cortical thickness ( Fujita et al, 2019 ; Kecskemeti et al, 2021 ; Mcguire et al, 2017 ) and diffusion metrics ( Acheson et al, 2017 ; Grech‐Sollars et al, 2015 ; Kamagata et al, 2015 ; Liu et al, 2014 ; Palacios et al, 2017 ; Prohl et al, 2019 ; Shahim et al, 2017 ; Veenith et al, 2013 ; Zhou et al, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…Table S1 for data sources), in which all three scanner types that were used in the test datasets were also represented (Philips Achieva, Philips Ingenia and Siemens Verio). Nonetheless, preprocessing of brain images already partly counteracts heterogeneity across scanners, as the ico brain software used to segment the MR images shows limited inter‐scanner variability [40, 41]. Therefore, this bias has been deemed to have been properly addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, preprocessing of brain images already partly counteracts heterogeneity across scanners, as the icobrain software used to segment the MR images shows limited inter-scanner variability [40,41]. Therefore, this bias has been deemed to have been properly addressed.…”
Section: Limitationsmentioning
confidence: 99%
“…ICC and CV expressed the similarity level across the observations of scans and the differences between scans, respectively. 17 Our study used ICC and CV to evaluate the difference of mean intensity and area of each same segmented tissue from different scans. ICC was computed using a two-way mixed method:…”
Section: Longitudinal Variability Measurementsmentioning
confidence: 99%